Tips for Success in Navigating a Master's Degree in Dance. Issue 2 (3rd April 2019) - Hogans, Azaria Rianne
ABSTRACT: In this article, I offer fourteen navigation tips on how to prepare for, traverse, and be successful in a master's program in dance. These navigation tips range from the social (getting outside of the dance department) to the practical (avoiding procrastination). I address the whole student including personal life, academic life, and professional life in seeking to ease the transition into graduate dance studies and navigate the next two to three years of school. The fourteen tips emerged from my personal experience and frequently asked questions.